Pengembangan Potensi Masyarakat dengan Penerapan Teknologi Mesin Pencacah Sampah Anorganik di Kelurahan Tanjung Pinggir - Munthe, Risma Nuraini; Napitu, Resna; Sri Martina; Tarigan, Vitryani; Ira Modifa (Universitas, 2022)
This community service activity aims to train and assist the Tanjung Pinggir village community in developing community potential through the use of inorganic waste counting machine technology. This activity's target audience consists of ten people from the Tanjung Pinggir village community in Pematangsiantar city. This activity is trained and mentored through lectures, demonstrations, and exercises, which are supplemented by questions and answers. The lecture method is used to explain business concepts and theories that are based on technology. The demonstration method is used to explain a future technology work process. While the training method is used to practice technology-based media, the question and answer method allows participants to consult on media development problems. The enthusiasm of the participants, pangulu, and activity funds aided in the implementation of this activity. The participants did not have prior knowledge of technology, and there was limited time for training. Participants can benefit from this service activity by increasing participant business sales